Excited state structural relaxation relaxation of N-(1-anthryl)-2,4,6-trimethyl-pyridinium cation - M. N. Khimich; N. I. Makarova; M. I. Knyazhansky; B. M. Uzhinov (International Journal of Photoenergy)
The fluorescence spectrum of N-(1-anthryl)-2,4,6-trimethylpyridinium cation (1) has an anomalously high Stokes' shift. The fluorescence spectra of 1 in ethanol and butyronitrile are shifted to shortwavelength region and fluorescence quantum yield increases as the temperature decreases. The fluorescence rate constant of this compound changes considerably (6 times in ethanol and 15 times in butyronitrile) as the temperature decreases from 293 K (relaxed state) to 77 K (mainly nonrelaxed state). It points out that at these temperatures the fluorescence takes place from two species with different structures. It is concluded that anomalously high fluorescence Stokes' shift of 1 is caused by both solvent orientation relaxation and excited state structural relaxation consisting in the mutual rotation of anthracene and pyridinium fragments of the cation and resulting in the formation of a specie with different structure. The rates of these processes are determined by the temperature-dependent viscosity of the medium.